Do Entrenched Managers Pay Their Workers More? - CRONQVIST, HENRIK; HEYMAN, FREDRIK; NILSSON, MATTIAS; SVALERYD, HELENA; VLACHOS, JONAS (Journal of Finance, 2009)
ABSTRACT Analyzing a panel that matches public firms with worker‐level data, we find that managerial entrenchment affects workers' pay. CEOs with more control pay their workers more, but financial incentives through cash flow rights ownership mitigate such behavior. Entrenched CEOs pay more to employees closer to them in the corporate hierarchy, geographically closer to the headquarters, and associated with conflict‐inclined unions. The evidence is consistent with entrenched CEOs paying more to enjoy private benefits such as lower effort wage bargaining and improved social relations with employees. Our results show that managerial ownership and corporate governance can play an important role for employee compensation.